HYDRODYNAMIC CHARACTERISTICS OF FUNCTIONAL CAVITATION DEVICES - Пузік, О.С.; Глазков, М.М.; Ланецький, В.Г.; Зайончковський, Г.Й.; Тарасенко, Т.В. (Proceedings of National Aviation University, 2012)
Proposed and justified method of calculating the parameters of functional cavitation devices. It was obtained summarized and calculated dependencies of critical parameters for determining leakage. Using the experimental data are built graphical dependencies for determining the capacity of the holes and nozzles.